Kinerja Keuangan Kopdit Kubu Gunung Tegaljaya di Desa Dalung Kecamatan Kuta Utara Kabupaten Badung - I PUTU ANDIKA SURYANATHA BUDI SENTANA; NYOMAN GEDE USTRIYANA; A.A.A. WULANDIRA SDJ (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2015)
ABSTRACT Financial Performance of Credit Cooperation of Kubu Gunung Tegaljaya at Dalung Village, Subdistrict of North Kuta, Badung Regency Cooperation is one of company which as according with constitution and fit with national economic structure of Indonesia. Financial analysis and horizontal vertical analysis to use looking for an issue arised and show development of credit cooperation business. This study aims to find out financial performance of credit cooperation of Kubu Gunung Tegaljaya with financial analysis and horizontal and vertical analysis in 2009 until 2013. data type has been collected that are quantitative and qualitative data. Method of data collection has been applied as follows: observation, interview, documentation, and literature study. Based on financial analysis, liquidity ratio and profitability ratio assumed bad, solvability ratio is good, and capital ratio is good. The result of the vertical analysis can be seen that become a component compiler assets on Kopdit Kubu Gunung Tegaljaya is assets smoothly, investment, and fixed assets, while the component compiler assets is a liability and equity. Horizontal analysis measured by using balance sheet and profit and loss experience improvement. Based on this study can be suggested the credit cooperation of Kubu Gunung Tegaljaya can press existing operational cost. Keyword: financial performance, financial analysis, horizontal and vertical analysis